Contributing factors of urban heat island- an investigation on surface temperature of ground surface materials in three plazas with different types of landscape settings : a case study of plazas in Putrajaya - Mohamad, Amira Nadhirah; Rozhan, Arinah; Mahamad Suhaimi, Mohd. Faiz; Abu Bakar, Aniza; Hj Mohd Ariffin, Noor Aziah (2012)
Urban heat island (UHI) is a phenomenon where an urban area is significantly warmer than its surrounding rural area (VoogtandOke, 2003). During night time, more heat is being released causing a greater temperature difference between the city and countryside. The increment of the air temperature is from the modification of land surface due to urban development such as change of land use, paved surfaces; more building being built that uses materials that significantly retain heat. Canyon geometry, evaporative cooling source and wind pattern are other factors that contribute to the formation of urban heat island. This phenomenon negatively affects the social outdoor activities, health and economy. Therefore, this paper aims to study the impact of surface material in urban plazas on their micro climate. Three different plazas: shaded, partially shaded and exposed plazas were studied to compare and contrast on their landscape settings and surface temperature of various materials. Other variables considered in this research are wind speed, solar radiation and cloud cover. By this research, it is hoped that appropriate surface material with appropriate criteria can be identified to mitigate the UHI effect.